Introducing Relational Values as a Tool for Shark Conservation, Science, and Management - Skubel, Rachel A.; Shriver-Rice, Meryl; Maranto, Gina M. (Frontiers in Marine Science, 2019)
Relational values (RV) are values that arise from a relationship with nature, encompassing a sense of place, feelings of well-being (mental and physical health), and cultural, community, or personal identities. With sharks, such values are formed by diverse groups that interact with these animals and their ecosystems, either physically or virtually, whether a scientist, student, fisher, or media-viewer. Further, these user groups may overlap or come into conflict over management plans, media portrayals of sharks, and their conservation status. Although scientists have not explicitly aimed to assess RV through sharks, qualitative studies of shark fishers, tourism operators, tourists, and the public, as well as historical and archeological accounts, can be interpreted through an analytical lens to reveal values which can also be defined as relational. To this end, this review considers studies capturing RV alongside those of economic value (increasingly, the value of a shark is appraised by their financial value in shark tourism) and the social and cultural roles of sharks. Based on these studies and the broader RV literature, we then outline a workflow for how RV can be leveraged in scientific inquiry, equitable resource management, and education. We conclude that via collaborative assessments of RV, with implicit inclusion of multiple values of sharks and by acknowledging their importance to all parties involved in user conflicts, the RV framework can lead to a constructive dialog on polarizing conservation and management issues. By illuminating shared values, and/or revealing dichotomies of values ascribed toward certain areas or objects, this framework can provide inroads to mediation, seeking to conserve or even restore relationships with nature, and their derived values as much as is possible. This approach can yield unexpected knowledge, solutions, and compromises in an increasingly complex conservation landscape.